2006
DOI: 10.2174/157340006778018184
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition Deficit in Schizophrenia: Accounting for Pragmatic Deficits in Communication Abilities?

Abstract: Schizophrenic individuals show impairments in language affecting what is referred to as the pragmatic component of language, typically the processing of non-literal language (e.g., irony, metaphor, indirect request). Such non-literal utterances require the ability to process the speaker's utterance beyond its literal meaning in order to allow one to grasp the speaker's intention by reference to the contextual information. This paper gives a selective literature review showing that different cognitive processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
(113 reference statements)
0
15
0
2
Order By: Relevance
“…First, our findings have potential implications for people suffering from communicative deficits. For example, schizophrenic individuals show impairments in the processing of non-literal language (e.g., irony, metaphor, indirect request), which requires the ability to process speakers' utterances beyond their literal meaning and to grasp their intention by reference to contextual information (Champagne-Lavau, Stip, & Joanette, 2006). Similar deficiencies have been documented for Parkinson's disease (Monetta, Grindrod, & Pell, 2009), right hemisphere damage (Abusamra, Côté, Joanette, & Ferreres, 2009), and autism (see Volkmar, Paul, Klin, & Cohen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, our findings have potential implications for people suffering from communicative deficits. For example, schizophrenic individuals show impairments in the processing of non-literal language (e.g., irony, metaphor, indirect request), which requires the ability to process speakers' utterances beyond their literal meaning and to grasp their intention by reference to contextual information (Champagne-Lavau, Stip, & Joanette, 2006). Similar deficiencies have been documented for Parkinson's disease (Monetta, Grindrod, & Pell, 2009), right hemisphere damage (Abusamra, Côté, Joanette, & Ferreres, 2009), and autism (see Volkmar, Paul, Klin, & Cohen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a deficit in the processing of such pragmatic aspects of language may be a significant factor in the social isolation experienced by many individuals with schizophrenia (SZ). SZ patients have been shown to exhibit pragmatic deficits, particularly deficits in understanding non-literal utterances such as irony, metaphor, or indirect requests that require the ability to process more than the literal meaning of an utterance in order to grasp the speaker's intention in a given context (see Champagne-Lavau, Stip, & Joanette, 2006;Mitchell & Crow, 2005 for exhaustive reviews of these deficits). Studies have also described pragmatic impairments in SZ patients such as failure to decode violations of conversational implicatures (Tenyi, Herold, Szili, & Trixler, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Given SZ patients' assorted impairments affecting the understanding of irony and metaphor, different cognitive processes such as intention decoding (e.g. ability to understand speaker's mental states such as intention or belief), executive dysfunction might be involved in such processing (Champagne-Lavau et al, 2006;Martin & McDonald, 2003). Therefore, a deficit in non-literal language understanding may reflect the presence of dysfunctions at different levels.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that SZ individuals have ToM impairments (Brune, 2005; Champagne-Lavau, Stip, & Joanette, 2006;Lee, Farrow, Spence, & Woodruff, 2004). However, a review of the literature concerning ToM impairments in SZ emphasises the complexity of the processes studied and the inherent difficulty of studying them.…”
Section: Introductionmentioning
confidence: 99%